PENGARUH IKLIM ORGANISASI, DISIPLIN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN PADA UPT. PERPUSTAKAAN UNIVERSITAS MULAWARMAN - Indra Hoki (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to determine the effect of organizational climate, work discipline and organizational communication on employee motivation at UPT. Mulawarman University Library. This type of quantitative associative research with a sample of 36 people which is a saturated sampling technique. The data sources used are primary data by means of interviews, distributing questionnaires and observation. While the analysis tool uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, Correlation Coefficient Analysis, Coefficient of Determination Analysis and Hypothesis Testing (T Test and F Test) with the help of the SPSS program. The test results are based on the results of the validity test, all statements of the research questionnaire are declared valid because r-count > r-table. For the reliability test, the Cronbach's Alpha value is also declared reliable because the Crobach's Alpha value > r-table. Based on the Multiple Linear Regression analysis, it is also stated that Organizational Climate, Work Discipline and Organizational Communication have a positive effect on Work Motivation. The Correlation and Determination Coefficient Test stated that there was a moderate relationship between Organizational Climate and Work Discipline variables on Work Motivation because the value of the correlation coefficient belonged to the coefficient interval between 0.040–0.599. As for the Organizational Communication variable, there is a strong relationship because the correlation coefficient value belongs to the coefficient interval between 0.060-0.799. Based on the partial hypothesis test (own) the results obtained that Organizational Climate, Work Discipline, Organizational Communication dominantly have a positive effect on Work Motivation. And simultaneously test the hypothesis (together) the results obtained that Organizational Climate, Work Discipline, Work Communication have a positive and significant effect on Work Motivation. Therefore H0 is rejected and H1 is accepted.